Geoculture – a Cultural Perspective on Geopolitics - Grosse, Tomasz Grzegorz (Chrześcijaństwo-Świat-Polityka, 2025)
The article presents a theoretical discussion on the relations between geopolitics and culture, especially with respect to the concepts of Feliks Koneczny and Samuel P. Huntington. It is therefore devoted to the idea of “​​clash of civilisations”, which is both a cultural and geostrategic phenomenon. The clash of civilisations concept has also a religious or ideological references, at least in relation to many geopolitical divisions. The research aim of the article is to transfer the theories of Huntington and Koneczny to the analysis of geocultural divisions in contemporary Europe. According to Huntington, the European Union is quite uniform, i.e. it represents Western culture. Nevertheless, the article presents cultural trends, which determine internal political cracks in the EU. There are even more geocultural divisions throughout the continent.